Calculations on Enhancement of Polycrystalline Diamond Bits through Addition of Superhard Diamond-Reinforced Elements - Boranbay Ratov; Miroslaw Rucki; Boris Fedorov; Edvin Hevorkian; Zbigniew Siemiatkowski; Samal Muratova; Elmira Omirzakova; Aidar Kuttybayev; Vladimir Mechnik; Nikolai Bondarenko (Machines, 2023)
The paper is dedicated to the enhancement of Polycrystalline Diamond Bits (PDC) designed for oil and gas industry. A novel diamond-reinforced composite was applied for cutting inserts, with the addition of 4 wt% chromium diboride to the WC-Co matrix. The addition of CrB2 ensured improvement of bending strength and fracture toughness by nearly 30% and 40%, respectively, and enhanced the diamond retention force. The efficiency of PDC bits was further improved by incorporating constructional features in both bottomhole and reaming parts. An analytical relationship between the feeding speed and geometrical parameters was found, including the wings and calibrating inserts numbers, as well as the rotational speed of the cutter. Under the conditions of rock fracture by reaming inserts, the approximate value of the required power was calculated.